Assessment of Solid Waste Characteristics and Waste Mitigation Strategies at Tanjung Priok Port - Diah Kartika Rahman; Gabriel Andari Kristanto (Jurnal Locus Penelitian dan Pengabdian, 2026)
Inefficient solid waste management contributes significantly to environmental degradation and marine debris pollution, particularly in port areas. Tanjung Priok Port, Indonesia’s largest port, handles intensive logistics activities that generate substantial waste from vessel operations, port services, and river-borne inputs. This study assesses the quantity, density, and composition of waste at three waste disposal sites to support sustainable management strategies. Sampling was performed over eight days following SNI 3964:2025. Waste sampling took place at three temporary waste storage sites (Tempat Penampungan Sementara, TPS) within the port area. TPS 01 recorded the highest waste generation (21.07 tons/day), followed by TPS 03 (3.59 tons/day) and TPS 02 (1.38 tons/day). Waste density ranged from 220.21 to 293.13 kg/m³, with organic waste, plastics, and paper comprising the dominant components. Statistical analysis confirmed significant differences among sites, highlighting spatial variability and the need for targeted mitigation measures. Waste characteristics at Tanjung Priok Port closely relate to the intensity of operational activities. TPS 01 shows the highest total amount at 168.59 tons, equivalent to an average of 21.07 tons per day, followed by TPS 03 with 28.68 tons (3.59 tons per day) and TPS 02 with 11.06 tons (1.38 tons per day).